Designing Right to Information Laws for Effective Implementation - Mendel, Toby (World Bank, Washington, DC, 2015)
This paper looks at the relationship between the design of a law which aims to give individuals a right to access information held by public authorities, i.e. a right to information (RTI) law, and the successful implementation of that law. The legal framework involves both laws and subordinate legislation, such as regulations, which complement the law and are easier to amend, with the result that there is likely to be a more dynamic relationship between the design of regulations and implementation challenges. There is also, of course, the question of how laws are interpreted by the courts, as well as other players, such as oversight bodies, which can impact significantly on implementation of the law. A key issue for this paper is the fact that there is, at least in many countries, a law-implementation or policy-practice gap in the sense that implementation of the RTI law is significantly sub-optimal.1 No law is perfectly implemented, but the gap between the standards of the formal rules and what actually happens is often quite significant for RTI laws. In some settings where observance of the rule of law is low, RTI laws are almost entirely ignored and/or certain key provisions in them are routinely ignored. This sort of radical policy-practice gap makes it difficult to discuss sensibly the relationship between legal design features and implementation, which is the focus of this paper. The paper therefore focuses on contexts where there is a reasonable expectation or an established record of medium to better practice in terms of implementation. A key focus is to discuss ways to reduce the policy-practice gap through more carefully tailored legal design.